Natalizumab-immunogenicity evaluation in patients with infusion related events or disease exacerbations - Ciano-Petersen, Nicolás Lundahl; Aliaga-Gaspar, Pablo; Hurtado-Guerrero, Isaac; Reyes, Virginia; Rodriguez-Bada, José Luis; Rodriguez-Traver, Eva; Brichette-Mieg, Isabel; Leyva Fernández, Laura; Serrano-Castro, Pedro; Alonso, Ana; Oliver-Martos, Begoña (Frontiers in Immunology, 2023)
Introduction: Natalizumab is a biologic drug for relapsing-remitting multiple sclerosis that may induce the generation of anti-drug antibodies in some patients. Anti-natalizumab antibodies (ANA) increase the risk of adverse events and reduce efficacy, being useful biomarkers for monitoring treatment response.Methods: Retrospective observational study including MS patients treated with natalizumab that experienced infusion-related events (IRE) or disease exacerbations (DE). ANA were tested by Elisa including a screening and a confirmation assay. Patients were further classified as transient (one positive result) or persistent (two or more positive results) ANA.Results: A total of 1251 MS patients were included and 153 (12.3%) had ANA with at least one single point determination, which were more frequent among patients with IRE compared to those with DE (21,6% vs.10.8%) during the first six infusions. Two or more determinations ANA were performed in 184 patients, being 31.5% permanently positive and 7.1% transiently positive. Interestingly, 26.1% of patients that experienced DE had persistent ANA, while 2.6% were transient. In contrast, 43% of patients with IRE had persistent ANA, and 9.3% had transient antibodies. Patients with persistent antibodies had more frequently high levels at the first sampling compared to patients with transient ANA.Conclusions: Real-world evidence shows that the presence of ANA is behind an important percentage of patients treated with natalizumab that experience IRE, as well as DE but in a lower degree. These findings support the need to systematically evaluate ANA towards a personalized management of these patients to avoid undesired complications.